ANALYSIS OF WORK SYSTEMS, RAW MATERIAL QUALITY AND AVAILABILITY IN FURNITURE COMPANIES - Harold, Rudi; Batekon, Erna Clara Rita; Podungge, Asti; Sapar, Lidyawati; Indah, Marhana Lia; Nur Rahman, Moh. Reyhan (Academic Solution Publisher, 2025)
This study aims to analyze the employee work system, the quality of wood raw materials, and the availability of work equipment at a small-scale furniture company in Gorontalo, considering that these three aspects play a crucial role in determining the quality and productivity of the furniture industry. This study used a qualitative descriptive method through in-depth interviews with five active workers, to describe the actual conditions of the production process, from wood selection, drying techniques, tool use, to product finishing. The results show that the quality of wood as a raw material is still assessed visually and without technical standards, which often results in shrinkage, cracks, and product defects. The drying process is carried out manually using sunlight, so production time is dependent on the weather and is unpredictable, slowing down the overall workflow. Furthermore, the company relies on manual tools and employees' personal tools, which not only prolongs processing time but also reduces quality consistency and increases the risk of production delays. These conditions are exacerbated by an informal work system and the absence of standard operating procedures (SOPs), resulting in unstructured quality control. Overall, this study concludes that the main obstacles to productivity lie in the quality of raw materials that are not standardized, limited production tools, and informal work structures, so that comprehensive improvements are needed through standardization of raw materials, improvement of work tools, and strengthening of operational procedures to achieve better production efficiency and quality.